Inovasi Metode Pendidikan Agama Islam Melalui Active Learning - Khairul Auliyah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
This article aims to equip students with the knowledge and techniques needed to solve problems using critical and logical thinking. This basic knowledge and problem solving techniques will be useful in their daily life. This study uses a descriptive qualitative approach. The purpose of this qualitative research is to describe actual facts or events without in-depth analysis to test hypotheses. The results showed that this method succeeded in instilling social, cognitive, and emotional skills in students. Students become more independent, have a strong leadership spirit, and have a responsibility to find solutions when facing problems. By using this method, students are encouraged to develop positive social behavior, teamwork, effective communication, expressing emotions and feelings, respecting diversity, and finding conflict resolution.